Host-interactor screens of Phytophthora infestans RXLR proteins reveal vesicle trafficking as a major effector-targeted process. Issue 5 (2nd March 2021) - Petre, Benjamin; Contreras, Mauricio P; Bozkurt, Tolga O; Schattat, Martin H; Sklenar, Jan; Schornack, Sebastian; Abd-El-Haliem, Ahmed; Castells-Graells, Roger; Lozano-Durán, Rosa; Dagdas, Yasin F; Menke, Frank L H; Jones, Alexandra M E; et al.
Abstract: Pathogens modulate plant cell structure and function by secreting effectors into host tissues. Effectors typically function by associating with host molecules and modulating their activities. This study aimed to identify the host processes targeted by the RXLR class of host-translocated effectors of the potato blight pathogen Phytophthora infestans . To this end, we performed an in planta protein–protein interaction screen by transiently expressing P. infestans RXLR effectors in Nicotiana benthamiana leaves followed by coimmunoprecipitation and liquid chromatography-tandem mass spectrometry. This screen generated an effector–host protein interactome matrix of 59 P. infestans RXLR effectors x 586 N. benthamiana proteins. Classification of the host interactors into putative functional categories revealed over 35 biological processes possibly targeted by P. infestans . We further characterized the PexRD12/31 family of RXLR-WY effectors, which associate and colocalize with components of the vesicle trafficking machinery. One member of this family, PexRD31, increased the number of FYVE positive vesicles in N. benthamiana cells. FYVE positive vesicles also accumulated in leaf cells near P. infestans hyphae, indicating that the pathogen may enhance endosomal trafficking during infection. This interactome dataset will serve as a useful resource for functional studies of P. infestans effectors and of effector-targeted host processes. Abstract : One-sentence summary In planta protein–protein interaction screen of Phytophthora infestans RXLR effectors by proteomics approach reveals host vesicle trafficking as a major effector-targeted process.